Isolation and characterisation of a gene for the T-Lymphocyte triggering factor from Trypanosoma vivax. - Khamadi, S.A. (University of Nairobi, 2000)
Abstract Early during infection of mice with T brucei parasites, the number of spleen mononuclear cells (MNCs) that produce interferon gamma (IFN-y) is increased and the parasite produces a molecule, aT-lymphocyte-triggering factor (TLTF), which in vivo in a rapid antigen-non-specific way, triggers CD8+ T-Iymphocyte cells to produce IFN-y. From such activated lymphoid MNCs, the parasite receives a growth stimulus (Olsson et ai., 1991). Antibodies against IFN-y abrogate this growth stimulus and recombinant rat IFN-y directly supports parasite growth indicating that the synthesised IFN-y may be a growth-stimulating factor for the parasite (Olsson et ai., 1991; Bakhiet et ai., 1993). The TLTF has been shown to bind directly to the CD8+ molecules on the T cells (Olsson et ai., 1991). IFN-y in turn induces the production of a mitogen-activated protein (MAP) kinase in African trypanosomes (Hua & Wang, 1997), which might be a factor contributing to the proliferation of trypanosomes in the bloodstream. Consistent with this possibility, a monoclonal antibody directed against TLTF reduces parasite levels and increase-(1he survival of mice infected with T brucei. The TLTF has been identified and characterised in T brucei. It has been shown by studies with the TLTF fused to the green fluorescent protein that TLTF is localised to the small vesicles that are found at or near the flagella pocket, the site of secretion in trypanosomes (Vaidya et ai., 1997). It has also been shown that T evansi, T gambiense and T rhodesiense also contain factor (s) with similar activity. Homogenates from these parasite taxa triggered mouse or rat MNCs of the lymphoid tissue to proliferate. These responses were dependent on CD8+ cells since the activity was (a) blocked by anti-CD8 antibodies and, (b) occurred in CD8+ enriched peripheral blood MNCs (Bakhiet et al., 1996). It was therefore important to determine whether livestock trypanosomes also have the gene for the TLTF and if so, whether it elicits the same immune response as seen in T brucei. In the study, T vivax genomic and cDNA expression libraries were screened using a T brucei rhodesiense TLTF probe. The TLTF gene in T vivax parasites was isolated by a novel technique referred to as Random PCR-assisted cloning of gene homologues. Studies on the expression of the gene in different life cycles of the parasite were also done. Northern hybridisation was done on the bloodstream and insect forms. The gene was found to be expressed in both life cycle stages. Southern hybridisation studies showed that the T vivax TLTF is a single copy gene.